PERANCANGAN SISTEM INFORMASI PSB PESANTREN Al HAMID CILANGKAP JAKARTA TIMUR - Efendi, Rustam; Syaechurodji, Syaechurodji; Juniansha, Dedi (Teknik Informatika Fakultas Ilmu Komputer, 2018)
The importance of education for every human being, because without education it is impossible for a human community to live to develop in line with their aspirations to progress, experience change, prosper and be happy as they see life. The higher the ideals of mankind increasingly demanded the improvement of the quality of education as a means of achievement. Al-Hamid's educational institution is a school that has advantages, namely: General education and boarding schools that educate students / students who are very unifying forms of thought patterns between formal and informal growing and this al-hamid boarding school is increasingly in demand from parents / guardians of the santri. The process of accepting new students (PSB) AL-HAMID is done by using Microsoft Excel, besides important documents in physical form (print out / hard copy ) only stored in folders or cabinets, storing separate and piling files creates difficulties in finding data and creating reports. By creating a new student admission information system PON-PES AL-HAMID uses borlan delphi 7 and MySQL, users can easily see, add, and update the data you want.